Sustainable Early English Language Education: Exploring the Content Knowledge of Six Chinese Early Childhood Education Teachers Who Teach English as a Foreign Language - Xiaobo Shi; Susanna Siu-sze Yeung (MDPI AG, 2024)
The importance of content knowledge (CK) for effective teaching and student learning is widely recognized. However, there is still a lack of detailed understanding of the CK held by early childhood education (ECE) teachers, particularly those teaching English as a foreign language (EFL). To fill this gap, our study utilized a qualitative approach, specifically stimulated recall classroom observation, to examine the various categories and subcategories of CK among Chinese EFL teachers in kindergartens. Six EFL teachers participated, two with English backgrounds and four with ECE backgrounds. Our findings highlight the multifaceted nature of CK in ECE EFL teaching, identifying three categories: knowledge of first language (L1) acquisition, knowledge of second language (L2) acquisition, and knowledge of linguistics. Notably, there were significant differences between the teachers with English and ECE majors, particularly in the most frequently mentioned CK subcategory and in how L1 is learned. This study not only illuminates these differences but also provides valuable insights for future research and practical applications in ECE EFL teacher education.